Chlorogenic acid modulates mitochondrial damage and mitophagy to repair injured myocardial tissue and cells - Ling, Hao; Zhang, Yu; Song, Chunli (Frontiers in Pharmacology, 2025)
BackgroundChlorogenic acid (CGA) is a polyphenolic compound widely present in plants. It is primarily extracted from the leaves of Eucommia ulmoides, a native medicinal herb.PurposeThis study aimed to investigate the cardioprotective effects of CGA on myocardial infarction (MI) by modulating mitochondrial damage and mitophagy through the PINK1/Parkin signaling pathway.MethodsIn vitro, H9C2 cardiomyocytes were treated with varying concentrations of CGA to assess cell viability, oxidative stress, mitochondrial function, and mitophagy markers (PINK1/Parkin) and mitophagic flux. In vivo, There are a total of 18 SD rats, which are randomly divided into Sham, MI, and CGA groups. MI was induced in SD rats via coronary artery ligation, followed by tail vein injection of CGA. Echocardiography, histological staining, electron microscopy, immunohistochemistry, Western blot (WB) and metabolomics analysis were conducted to evaluate cardiac function, tissue fibrosis, mitophagy, and metabolic changes.ResultsCGA significantly improved cell viability and reduced oxidative stress in H9C2 cells. It also stabilized mitochondrial membrane potential, increased ATP levels, upregulated PINK1/Parkin expression and increase autophagy flux, Lysosomal inhibitor treatment elevates expression of Parkin, P62 and LC3-II. In MI rats, CGA reduced ROS levels, improved myocardial tissue integrity, reduced fibrosis, and enhanced cardiac function. Detected by electron microscopy, immunohistochemistry, and WB confirmed increased mitophagy in CGA-treated rats. Metabolomics analysis revealed significant alterations in metabolic pathways, particularly related to organic acids and amino acid metabolism.ConclusionThis study demonstrates that CGA exerts cardioprotective effects by modulating mitochondrial damage and promoting mitophagy through the PINK1/Parkin pathway. Our findings provide new insights into the therapeutic potential of CGA for MI treatment and suggest a promising natural compound for myocardial protection.